ผลของโซเดียมเมตาไบซัลไฟต์ โซเดียมเฮกซะเมตาฟอสเฟต และกรดซิตริกต่อการเปลี่ยนแปลงคุณภาพของหอยเป๋าฮื้อ Haliotis asinina L. บรรจุกระป๋อง - กลางกมล จันทราสุทธิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
To study the effects of sodium metabisulfite, sodium- hexametaphosphate and citric acid on quality changes of canned abalone Haliotis asinina L. Fresh abalone meat used in this study had 84% moisture, 12.74% proteins, 0.62% fats and 1.02% ash. Optimum process times was studied. Abalone (220 g net weight) was packaged in a 307x113 can, and sterilized at 121 ํC to attain Fo = 4 min.The predicted process time at 121 ํC retort temperatures was 11.50 min. The effect of soaking times was studies,Abalone was soaked in 0.1% sodium metabisulfite and 5% sodium hexametaphosphate solution at 0 5 10 and 15 min. As soaking time increased, degree of browning of abalone tended to decrease and water-holding capacity and cutting force tended to increase. However soaking time at 10 min not difference from 15 min. The optimum condition for soaking abalone was determined from degree of browning and water-holding capacity. The optimum condition was 10 min. The study of concentration of citric acid on quality changes of canned abalone was studied. Abalone was soaked in 0.1% sodium metabisulfite and 5% sodium hexametaphosphate at 10 min and added 0 0.05 0.1 and 0.2% citric acid in brine solution. The results from color measurement (L-value) of abalone, abalone added citric acid in brine had significantly higher (p <= 0.05) than that without citric acid solution. The degree of browning of abalone with addition of 0.2% citric acid was lower than those added 0 0.05 and 0.1 respectively. The canned abalone added 0.2% citric acid in brine was the optimum The accelerated shelf life test was done at 35 and 45 ํC. The color, cutting force and degree of browning of the product increase with increased storage period. The predicted shelf life of the canned abalone in brine at 30 ํC was 137.19 days.